2018
DOI: 10.1021/acs.chemmater.8b01455
|View full text |Cite
|
Sign up to set email alerts
|

Kirkendall Effect: Main Growth Mechanism for a New SnTe/PbTe/SnO2 Nano-Heterostructure

Abstract: Attention to semiconductor nanostructures with a narrow band gap energy and low production cost has increased in recent years, due to practical demands for use in various optoelectronics and communication devices. Colloidal nanostructures from the IV–VI semiconductors, such as lead and tin chalcogenides, seem to be the most suitable materials platform; however, their poor chemical and spectral stability has impeded practical applications. The present work explored the mechanism for formation of new nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…This healing permits synthesis procedures at low temperatures, , induces considerable tolerance for the existence of stoichiometric or crystallographic defects, , and may be a basis for doping or alloying processes. Indeed, the APbBr 3 NCs exhibit intriguing optical properties, appearing as narrow emission bands, bright emission with high quantum yields (QYs), and anharmonic contributions to distinct physical effects. ,, The emission energy from APbX 3 NCs can easily be tailored postsynthetically over the entire visible spectral range, by adjusting their halide composition via anion-exchange, while preserving the particles’ size and shape. , In the field of II–VI and IV–VI semiconductor colloidal NCs, cation-exchange is a very common technique, endowing them with diverse compositions which are difficult to achieve otherwise. For APbX 3 perovskites, however, cation exchange strategies are still in an early stage of research, even though exchanging A + and/or Pb 2+ by other cations might enable better control over NC properties. In one of the few studies available, Akkerman et al successfully managed to replace Cs + with MA + or FA + . , Attempts to perform a partial exchange of Pb 2+ cations preliminary were motivated by the need to reduce the level of toxicity of Pb-compounds .…”
mentioning
confidence: 99%
“…This healing permits synthesis procedures at low temperatures, , induces considerable tolerance for the existence of stoichiometric or crystallographic defects, , and may be a basis for doping or alloying processes. Indeed, the APbBr 3 NCs exhibit intriguing optical properties, appearing as narrow emission bands, bright emission with high quantum yields (QYs), and anharmonic contributions to distinct physical effects. ,, The emission energy from APbX 3 NCs can easily be tailored postsynthetically over the entire visible spectral range, by adjusting their halide composition via anion-exchange, while preserving the particles’ size and shape. , In the field of II–VI and IV–VI semiconductor colloidal NCs, cation-exchange is a very common technique, endowing them with diverse compositions which are difficult to achieve otherwise. For APbX 3 perovskites, however, cation exchange strategies are still in an early stage of research, even though exchanging A + and/or Pb 2+ by other cations might enable better control over NC properties. In one of the few studies available, Akkerman et al successfully managed to replace Cs + with MA + or FA + . , Attempts to perform a partial exchange of Pb 2+ cations preliminary were motivated by the need to reduce the level of toxicity of Pb-compounds .…”
mentioning
confidence: 99%
“…As noted above, SnTe NC oxidation has been reported by others, and some have suggested that the capping ligands may be a possible source of oxidation. 11 , 15 To investigate this hypothesis, a single synthesis was conducted with analysis of NC products formed pre- and post-OA injection. The resulting products were purified under differing conditions, producing NCs that were (1) OA capped and purified in ambient atmosphere, (2) OA capped and purified under an inert atmosphere, and (3) OAm capped and purified under an inert atmosphere ( Figures 1 (b), 2 (a–f), and S1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 13 , 14 Such stoichiometric or near-stoichiometric NC compositions suggest a lack of SnO x formation; however, an amorphous tin-rich surface oxide is known to form. 11 , 15 In contrast, an investigation of tin chalcogenide oxidation using 119 m Sn Mössbauer spectroscopy reported SnTe NCs having a Sn(IV):Sn(II) ratio of 1.2:1 (i.e., 55:45%). 18 While quantitatively in agreement with bulk studies using XPS, 16 , 17 if we estimate the overall NC composition as being derived from Sn 4+ O 2 and Sn 2+ Te, these results imply a Sn:Te composition of 2.2:1, which is inconsistent with compositions measured via EDS.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the Kirkendall effect was known as an atomic diffusion phenomenon caused by the concentration difference, which took place when diffusion rates between two exchanged species were different (Cu 0 and Cu + in this case). 21,22 The obvious concentration difference for Cu 0 and Cu + on each side of the interface established in the Cu@Cu 2 O core@shell NPs could trigger their interdiffusion. The diffusion rate of the outward Cu 0 was much faster than the rate of inward Cu + , giving rise to the outward-direction flux of the inner Cu 0 core and an inward-direction flow of vacancies to generate internal pores in the Cu core side (Figure S3).…”
Section: Resultsmentioning
confidence: 99%